Reliability on the Internet of Things with designing approach for exploratory analysis - Singh, Khushwant; Yadav, Mohit; Singh, Yudhvir; Barak, Dheerdhwaj; Saini, Ashish; Moreira, Fernando (Frontiers in Computer Science, 2024)
The Internet of Things (IoT) proposes to transform human civilization such that it is smart, practical, and highly efficient, with enormous potential for commercial as well as social, and environmental advantages. Reliability is one of the major problems that must be resolved to enable this revolutionary change. The reliability issues raised with specific supporting technologies for each tier according to the layered IoT reliability are initially described in this research. The research then offers a complete review and assessment of IoT reliability. In this paper, various types of Reliability on the Internet of Things have been analyzed with each layer of IoT to solve the issues of failure rates, Latency, MTTF, and MTBF. Each parameter has a certain classification and perception as well as enhancement in efficiency, accuracy, precision, timeliness, and completeness. Reliability models provide efficient solutions for different IoT problems which are mirrored in the proposed work and classified with four types of reliabilities. The field of IoT reliability exploration is still in its initial phases, despite a sizable research record. Further, considering the recent case study of CHISS is elaborated with discovered behaviors including brand-new aspects like the multifaceted nature of evolving IoT systems, research opportunities, and difficulties.